2015
DOI: 10.1016/j.jim.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous assessment of NF-κB/p65 phosphorylation and nuclear localization using imaging flow cytometry

Abstract: Aberrant activity of Nuclear Factor–kappaB (NF-κB) is associated with many diseases and is therapeutically targeted. Post-translational modifications, particularly phosphorylation of the RELA/p65 sub-unit, are essential for cytoplasmic to nuclear localization of NF-κB/p65 and initiation of transcription of downstream target genes. Immunoblot and phospho-flow cytometry has been used to study the relationship between phosphorylation motifs and NF-κB activation and microscopic analysis of nuclear localization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…It was previously shown that okadaic acid, an inhibitor of PP1 and PP2A, provoked NF-B phosphorylation in MG63 human osteosarcoma cells, but the specific contribution of PP1␣ was not explored (30). In our study, costimulation-related NF-B activity was determined by measuring the phosphorylation (Ser529) of the p65 subunit and its translocation to the nucleus by imaging flow cytometry (31)(32)(33). While costimulation induced the phosphorylation of NF-B (p65) in control siRNA-treated cells, this phosphorylation was completely inhibited in the PP1 KD cells ( Fig.…”
Section: Figmentioning
confidence: 88%
“…It was previously shown that okadaic acid, an inhibitor of PP1 and PP2A, provoked NF-B phosphorylation in MG63 human osteosarcoma cells, but the specific contribution of PP1␣ was not explored (30). In our study, costimulation-related NF-B activity was determined by measuring the phosphorylation (Ser529) of the p65 subunit and its translocation to the nucleus by imaging flow cytometry (31)(32)(33). While costimulation induced the phosphorylation of NF-B (p65) in control siRNA-treated cells, this phosphorylation was completely inhibited in the PP1 KD cells ( Fig.…”
Section: Figmentioning
confidence: 88%
“…Then NF‐κB migrates into the nucleus and activates gene expression . Following activation, the peak of NF‐κB nuclear localization occurs at 30 min . Therefore, the cells were treated with LPS for 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…36 Following activation, the peak of NF-κB nuclear localization occurs at 30 min. 37 Therefore, the cells were treated with LPS for 30 min. The results in our study showed that LPS induced NF-κB translocating from cytoplasm to nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial relationship between the transcription factors and nuclear images was measured using the ‘Similarity’ feature in the IDEAS software to quantitate the mean similarity score in the cell populations per sample. A similarity score >1 represents nuclear translocation, and the shift in distribution of nuclear translocation between two samples was calculated using the Fisher’s Discriminant ratio (Rd value) (Maguire et al , 2015).…”
Section: Methods and Protocolsmentioning
confidence: 99%